Pengaruh Informasi Akuntansi, Risk Perception dan Herding terhadap Keputusan Investasi - Chika Yanda Permata Putri; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2022)
This research aimed to examine the effect of accounting information, risk perception, and herding on investors' investment decisions in the capital market. A quantitative method was employed by the authors in this research. The researchers utilized questionnaires to collect the data. There were 96 investor respondents who participated as a research sample in this study. The respondents in this study are investors registered in securities companies in the capital market and several investment galleries. The researchers used SPSS as statistical test software to process research data. Meanwhile, the reliability and validity tests were used by researchers to test whether the research questionnaire was valid and reliable. The researchers conducted hypothesis testing, multiple linear regression analysis, and classical assumption test as research analysis methods. The findings of this study show that investors' investment decisions in the capital market are positively influenced by herding and accounting information. Meanwhile, investors' investment decisions in the capital market are not significantly influenced by perceived risk.